Pengembangan Aplikasi Pencarian Lokasi Pabrik Tahu di Kota Depok Berbasis Android Menggunakan Metode Location Based Service (LBS) dengan Android Studio (Yayasan Kawanad, 2024)
In this modern era, technology is advancing rapidly, allowing for the search of tofu factories using smartphones. This study aims to develop an application to locate tofu factories in Depok City utilizing GIS (Geographic Information System) technology and GPS (Global Positioning System) integrated with the Android Google Maps platform. The application is designed to facilitate the public in finding the nearest tofu factory locations. This Android-based tofu factory search application employs Location Based Service (LBS) methods to provide real-time location information. The primary objective of this research is to simplify the process for the community in Depok to find tofu factories, thereby improving efficiency and saving time. Additionally, this application is expected to assist tofu factory owners in attracting more customers by providing accurate and accessible location information. The methodology includes literature review, direct observation, and application development using Java programming language in Android Studio. The results show that the application significantly simplifies the process for the community in Depok to find tofu factories, improving efficiency and saving time. Furthermore, the application is expected to assist tofu factory owners in attracting more customers by providing accurate and accessible location information